Cyclodextrins as effective additives in AuNP-catalyzed reduction of nitrobenzene derivatives in a ball-mill. Issue 20 (19th July 2016) - Menuel, S.; Léger, B.; Addad, A.; Monflier, E.; Hapiot, F.
Abstract : At the boundary between mechanochemistry, supramolecular chemistry and catalysis, the present study explores the role of cyclodextrins (CDs) and other saccharide additives in the mechanosynthesis of gold nanoparticles (AuNPs) and their use as catalysts in the reduction of substituted nitrobenzene derivatives. Abstract : At the boundary between mechanochemistry, supramolecular chemistry and catalysis, the present study explores the role of cyclodextrins (CDs) and other saccharide additives in the mechanosynthesis of gold nanoparticles (AuNPs) and their use as catalysts in the reduction of substituted nitrobenzene derivatives into their corresponding aniline products. CDs not only allow for the stabilization of the AuNPs but also help diffuse a substrate within a solid mixture via supramolecular means, and orient the chemical reaction to the selective formation of aniline derivatives. Parameters influencing both the formation of AuNPs and the synthesis of aniline derivatives have been investigated. We show that the catalytic performance strongly depends upon the nature of the saccharide additive, the nature and location of the substituent on the benzene, and the ball-milling conditions. Water also plays a key role in both the reduction mechanism of the nitro groups and the supramolecular interactions with the substrate. Very interestingly, the amount of reductive agent (NaBH4 ) was drastically reduced compared to reductions performed in solution. Additionally, the catalytic system could be recycled over three consecutive runs without significant loss in activity, thus highlighting the efficacy of the combination of mechanochemistry, supramolecular chemistry, and catalysis.